Cation functional group effect on SO2 absorption in amino acid ionic liquids - Siami, Hasan; Razmkhah, Mohammad; Moosavi, Fatemeh (Frontiers in Chemistry, 2023)
The effect of the functional group of cation on SO2 acidic gas absorption by some designed amino acid ionic liquids (AAILs) was studied. An isolated pair of glycinate anion and pristine imidazolium-based cation, as well as decorated cation functionalized by hydroxyl (OH), amine (NH2), carboxylic acid (COOH), methoxy (OCH3), and acetate (CH3COO) groups, were structurally optimized by density functional theory (DFT) using split-valence triple-zeta Pople basis set. The binding and Gibbs free energy (Gint) values of SO2 absorption show the AAIL functionalized by the COOH group is the most thermodynamically favorable green solvent and this functional group experiences the closest distance between anion and captured SO2 and vice versa in the case of cation … SO2 which may be the main reason for being the best absorbent; in addition, the highest net charge-transfer amount of SO2 is observed. Comparing the non-covalent interaction of the systems demonstrates that the strongest hydrogen bond between captured gas and anion, as well as -hole, and van der Waals (vdW) interaction play critical roles in gas absorption; besides, the COOH functional group decreases the steric effect while the CH3COO functional group significantly increases steric effect after absorption that declines the hydrogen bond.